ANALISA PENGELOLAAN MODAL KERJA GUNA MENILAI TINGKAT LIKUIDITAS PADA PT. HM SAMPOERNA - Dania Puspitasari (Jurnal Ilmiah Akuntansi Indonesia, 2017)
Abstract: The aim of this study was analisys the effect of working capital and the effect of receivables turnover to liquidity rate. Working capital and receivables turnover was an inportant thing for companies to its daily trading expenses. Available working capital must be effectively to conserve liquidity.This study used data of Current Ratio, Quick Ratio, and  Cash Ratio to capital working on  PT. HM. Sampoerna period 2014-2016. This study proves that estimation of regresion model showed that independent variabel that used have effect to working capital on PT HM Sampoerna. Effect of Three variabel on this studied had 68,5% while the rest effected by other factor out of this studied.Keywords : Cash Ratio, Current Ratio, Liquidity, Quick Ratio, Working Capital